2020
DOI: 10.1182/blood-2020-136928
|View full text |Cite
|
Sign up to set email alerts
|

TAK-169, a Novel Recombinant Immunotoxin Specific for CD38, Induces Powerful Preclinical Activity Against Patient-Derived Multiple Myeloma Cells

Abstract: Monoclonal antibodies (daratumumab, anti-CD38; elotuzumab, anti-SLAMF7) and BCMA-targeting T-cell redirecting therapies are highly effective in a large proportion of multiple myeloma (MM) patients. Nonetheless, age, prior (chemo)therapy, and the tumor-microenvironment may impair immune effector cell function and therefore significantly reduce the efficacy of these immunotherapies. Alternatively, an appealing strategy would be the use of targeted therapies, such as immunoconjugates, that directly kill the tumor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Preclinical studies demonstrated highly effective lysis of primary MM cells in vitro . 21 No clinical data regarding the ongoing phase I study (NCT04017130) are yet available. TAK-573 targets a CD38 epitope for which cross-reactivity with the currently approved anti-CD38 monoclonal antibodies, daratumumab and isatuximab, is not anticipated.…”
Section: Antibody-drug Conjugatesmentioning
confidence: 99%
“…Preclinical studies demonstrated highly effective lysis of primary MM cells in vitro . 21 No clinical data regarding the ongoing phase I study (NCT04017130) are yet available. TAK-573 targets a CD38 epitope for which cross-reactivity with the currently approved anti-CD38 monoclonal antibodies, daratumumab and isatuximab, is not anticipated.…”
Section: Antibody-drug Conjugatesmentioning
confidence: 99%
“…TAK-169 and TAK-573 are ADCs targeting CD38, which is highly expressed on the surface of MM cells. These ADCs aim to deliver cytotoxic payloads specifically to CD38-expressing cells, thereby inhibiting tumor growth and inducing cell death [ 198 , 199 ]. DFRF4539A is an ADC targeting FcRH5, also known as Fc receptor homolog 5.…”
Section: Targeted Immunotherapymentioning
confidence: 99%
“…In pre-clinical studies, this agent induced irreversible ribosome inactivation and potent cytotoxicity against CD38-positive human myeloma models [68]. Among tested primary samples, TAK-169 was equally effective against plasma cells from patients with newly diagnosed and relapsed/refractory myeloma, though a fraction of cells from daratumumab-refractory patients were less sensitive [69]. A very preliminary report of the Phase I study in four patients with relapsed/refractory myeloma and at least 5 prior LOT noted one TEAE of asymptomatic Grade 2 reversible myocarditis and Grade 3 troponin elevation [70], raising concern about its further development.…”
Section: Mt-0169mentioning
confidence: 99%